Properhyssalus, a new fossil genus of braconid wasps close to the genus Rhyssalus Haliday (Hymenoptera: Braconidae: Rhyssalinae) from Baltic amber - Belokobylskij, Sergey A.; Manukyan, Andranik R. (Zootaxa, 2024)
The new braconid genus and species from the subfamily Rhyssalinae, Properhyssalus szechowskii Belokobylskij, gen. et sp. nov., from late Eocene Baltic amber are described and illustrated. The differences between the new genus and the type species of Rhyssalus Haliday, 1833, Rh. clavator Haliday, 1833, are provided. The position of the previously described from Baltic amber species Rhyssalus brevicornis Brues, 1933 and Rh. rugosus Brues, 1933, as well as Palaeorhyssalus dubitosus Brues, 1933, are discussed.